2018
DOI: 10.1038/s41396-018-0158-1
|View full text |Cite
|
Sign up to set email alerts
|

A strong link between marine microbial community composition and function challenges the idea of functional redundancy

Abstract: Marine microbes have tremendous diversity, but a fundamental question remains unanswered: why are there so many microbial species in the sea? The idea of functional redundancy for microbial communities has long been assumed, so that the high level of richness is often explained by the presence of different taxa that are able to conduct the exact same set of metabolic processes and that can readily replace each other. Here, we refute the hypothesis of functional redundancy for marine microbial communities by sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
142
3
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(165 citation statements)
references
References 46 publications
(67 reference statements)
15
142
3
1
Order By: Relevance
“…This is further corroborated by the significant positive correlation between the community structure and relative abundance of pathways. These results further indicate the coexistence of organisms with the Red Sea community that share specific functions, but differ in other ecological requirements, as has been previously suggested for the planktonic community (Galand, Pereira, Hochart, Auguet, & Debroas, ). As bacteria are vital in the functioning of coral reef ecosystems (Ainsworth et al, ), understanding the degree of functional redundancy is critical to better understand how species loss will ultimately affect coral reefs.…”
Section: Discussionsupporting
confidence: 86%
“…This is further corroborated by the significant positive correlation between the community structure and relative abundance of pathways. These results further indicate the coexistence of organisms with the Red Sea community that share specific functions, but differ in other ecological requirements, as has been previously suggested for the planktonic community (Galand, Pereira, Hochart, Auguet, & Debroas, ). As bacteria are vital in the functioning of coral reef ecosystems (Ainsworth et al, ), understanding the degree of functional redundancy is critical to better understand how species loss will ultimately affect coral reefs.…”
Section: Discussionsupporting
confidence: 86%
“…For marine prokaryotes, the results are more contrasted. Some studies report a decoupling between the metabolic potential and taxonomic composition, which has been attributed to a high functional redundancy (Sunagawa et al, 2015;Louca et al, 2016); reversely, other authors showed strong covariations between the taxonomy of prokaryotes and their metagenome across distinct samples, challenging functional redundancy (Galand et al, 2018). These divergences stress the need for a common approach, a common definition and tests across distinct scales to answer the debate over microbial functional redundancy.…”
Section: Coupling Between Functional Roles and Taxonomy Among Marine mentioning
confidence: 99%
“…taxonomic diversity) would be independent and driven by dispersal and biotic interactions (Louca et al, 2018). This paradigm is still being debated (Galand et al, 2018) and, as for now, has excluded protists due to the present limitations in the genome analysis of microeukaryotes (Keeling and del Campo, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Our observations thus fit well with a scenario of widespread functional redundancy [39,90], 23 395 400 405 410 with intra-species diversity guaranteeing the persistence of species -and therefore functional stabilityacross environmental gradients. The idea of functional redundancy has been recently challenged by using OTUs-97% as the units of diversity [91]. As shown in this study, that resolution fails to capture the complex dynamics occurring at the sub-species level, which seem to be widespread -at least in freshwater lakes -and some of which might contribute to functional redundancy [76].…”
Section: Discussionmentioning
confidence: 92%